FINANCIAL LITERACY AND FINANCIAL ATTITUDE ON FINANCIAL MANAGEMENT BEHAVIOR WITH GENDER AS A MODERATED VARIABLE - Susilo, Budi; Indira, Irma; Rodhiyah, Ma’rufatur (LP2M Universitas Bina Bangsa, 2025)
This study seeks to investigate the influence of financial literacy and financial attitudes on financial management behavior, with gender serving as a moderating variable. This research is quantitative. The study population comprised 678 undergraduate accounting students at Lamonganfinan, with a research sample of 88 students. The employed sampling technique was simple random sampling, utilizing a questionnaire for data collection. The study's data were analyzed utilizing the SmartPLS 3 software application, which serves as an analytical tool. This study shows that financial literacy positively and significantly influences the financial management behavior of undergraduate accounting students in Lamongan, however financial attitudes do not significantly affect their financial management behavior. Gender exerts a positive and significant influence on the financial management behavior of undergraduate accounting students in Lamongan. Gender does not influence the impact of financial literacy on the financial management of undergraduate accounting students in Lamongan